Republic of Serbia : Fourth Review under the Policy Coordination Instrument-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2020)
Recent economic developments. Notwithstanding a sizeable policy response, the COVID-19 pandemic is having a significant adverse impact on Serbia's economic activity, with output in 2020 projected to contract by 3 percent, compared to a 4 percent increase expected prior to the COVID-19 shock. The shock is affecting the economy through lower external demand, weaker foreign direct investment and remittances, disruptions in regional and global supply chains, and domestic supply constraints. The government took strong actions to contain the pandemic at an early stage, but the number of infections accelerated again towards end-June. As a result, some containment measures have been re-introduced.